PENGARUH KOHESIVITAS TIM DAN KOMITMEN PADA TUJUAN TERHADAP KINERJA MANAJERIAL DENGAN DIMEDIASI HIGH PERFORMANCE WORK SYSTEM PADA PERUSAHAAN PENERBITAN BUKU DI JAWA TENGAH - maskudi, Maskudi (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
ABSTRACT The main purposes of this research is to study the impact of team cohesiveness, commitment to goals towards managerial performance mediated by high performance work systems construct at cooperatives in Semarang City, Province of Central Java, Indonesia. Based on the main purpose this research is an applied research descriptive correlative based on data collected which had been done in 2019. The population in this study were members of the creative editorial team or group in book publishing at a book publishing company in Central Java, as many as 1,970 people with 150 managers taken as samples. To analyze the data used Structural Equation Modeling (SEM) analysis. The result of hypothesis’ examination shows that team cohesiveness, commitment to goals and high performance work system construct have a significant positive influence towards manajerial performance Key Words: Team Cohesiveness, Commitment to Goals, High performance Work System and Managerial Performance.